Integration of Islamic Boarding School Curriculum Based on Islamic Values and Technology in Indonesia - Elhaq Zainur Rochim; Afiful Ikhwan; Syamsul Arifin; Cantik Tri Rahajeng (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the model of integration of Islamic boarding school curriculum based on Islamic values ​​and technology at Pesantren Sintesa Magetan, which combines religious learning and digital skills in one integrated education system. This study uses a qualitative approach with a case study method, collecting data through in-depth interviews, participatory observation, and documentation, involving caregivers, teachers, and students. The results of the study indicate that the Pesantren Sintesa curriculum integrates tahfidz teaching, book studies, and digital skills such as digital marketing, web management, and multimedia simultaneously, with project-based learning facilitated by mentors. This model is effective in improving the technical, soft, and conceptual skills of students, as well as forming graduates who are ready to compete professionally without losing their Islamic identity. The challenges faced include differences in basic digital skills of students, limited infrastructure, and the need for competent teachers, which are overcome through intensive mentoring and the use of online teachers. This study recommends strengthening technology-based teacher training, developing a flexible curriculum that is adaptive to digital developments, and replicating this integration model in other Islamic boarding schools to produce a generation of Muslims who are globally competitive. These findings are expected to be the basis for the development of technology-based Islamic education in the Society 5.0 era.